Approaching the community about screening children for a multicentre malaria vaccine trial - Lang, T; Gould, J; von Seidlein, L; Lusingu, J; Mshamu, S; Ismael, S; Liheluka, E; Kamuya, D; Mwachiro, D; Olotu, A; Njuguna, P; Bejon, P; et al. (2012)
Community sensitisation, as a component of community engagement, plays an important role in strengthening the ethics of community-based trials in developing countries and is fundamental to trial success. However, few researchers have shared their community sensitisation strategies and experiences. We report on our perspective as researchers on the sensitisation activities undertaken for a phase II malaria vaccine trial in Kilifi District (Kenya) and Korogwe District (Tanzania), with the aim of informing and guiding the operational planning of future trials. We report wide variability in recruitment rates within both sites; a variability that occurred against a backdrop of similarity in overall approaches to sensitisation across the two sites but significant differences in community exposure to biomedical research. We present a range of potential factors contributing to these differences in recruitment rates, which we believe are worth considering in future community sensitisation plans. We conclude by arguing for carefully designed social science research around the implementation and impact of community sensitisation activities. © 2011 Royal Society of Tropical Medicine and Hygiene.